Contrasting multiple models of brand equity’s role in consumer decision making - Hilgenkamp, Heather (Kansas State University, 2014)
Brand Equity is a common phrase in consumer research, but there is still a lot of ambiguity surrounding the measurement of this concept (Keller, 2008). Several methods of measurement have been proposed over the years, but no one method has been adopted as the ideal way to predict purchase intent and measure brand equity. The current research tested three theories—Social Exchange Theory (SET), Theory of Planned Behavior (TPB), and the Yoo and Donthu model—to see which is the best predictor of purchase intent and brand equity. SET assumes consumers weigh the costs and rewards of purchasing the product. TPB uses consumers’ attitudes over purchasing the product, subjective norms of what others would do, and the perceived behavioral control consumers have in actually purchasing the product. The Yoo and Donthu model has been used most often of the three theories in measuring brand equity and includes measures of brand loyalty, perceived quality, brand awareness/associations, and overall brand equity. Study 1 assessed consumer durable products (TV and athletic shoes) and Study 2 assessed consumer non-durable products (soap and toothpaste). Consumers evaluated these products online based on a picture of the product, the brand name, price, customer reviews, quality ratings, and an advertisement and then indicated their likelihood to purchase the product. Theory of Planned Behavior was the best predictor of purchase intent across all four products assessed indicating that consumers look at external factors such as what others would do as well as how much control they have over purchasing the product as much as they consider their own attitudes.
Keywords: Brand equity; Theory of planned behavior; Social Exchange Theory; Yoo and Donthu model of brand equity; Purchase intent; Cognitive Psychology (0633); Marketing (0338); Psychology (0621)